Young British Muslims: Identity, Culture, Politics and the Media - Kabir, Nahid Afrose (© 2010 Edinburgh University Press, 2019)
This book was published by Edinburgh University Press, 2010. Open access to this book available at https://www.jstor.org/stable/10.3366/j.ctt1r1xzn